Electrolytes and lithium metal batteries

By using a specific molar ratio of sulfonylimide lithium salts and fluoroborate lithium salts, along with a chlorinated linear ether solvent with a specific structure, stable SEI and CEI films are formed in lithium metal batteries, solving the problem of insufficient electrolyte interface stability and improving the long-cycle performance of lithium metal batteries.

CN122638580APending Publication Date: 2026-08-25SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610820713.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-08
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

The interfacial stability of the electrolyte in existing lithium metal batteries is insufficient, resulting in poor capacity retention and decay of coulombic efficiency in lithium copper half-cells during long-term cycling.

Method used

A composite lithium salt system composed of sulfonylimide lithium salt and fluoroborate lithium salt in a specific molar ratio is used, combined with a linear ether solvent and a chlorinated linear ether solvent with a specific structure, to form stable SEI and CEI films, suppressing lithium dendrite growth and interfacial side reactions.

Benefits of technology

It improves the ion conductivity of the electrolyte, enhances the stability of the electrode interface, reduces the loss of active lithium during cycling, and improves the capacity retention of lithium metal batteries under high voltage and long cycling conditions and the coulombic efficiency of lithium copper half-cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122638580A_ABST
    Figure CN122638580A_ABST
Patent Text Reader

Abstract

The application provides an electrolyte and a lithium metal battery, and relates to the technical field of lithium metal batteries.The electrolyte comprises a lithium salt and an ether solvent; the lithium salt comprises a sulfoximine lithium salt and a fluoroboric acid lithium salt in a molar ratio of 1: (0.1-0.5); the ether solvent comprises a linear ether solvent and a chlorinated linear ether solvent; the linear ether solvent comprises at least one of 1,2-dimethoxypropane, 1,3-dimethoxypropane, 1,2-diethoxyethane and 1-methoxy-2-ethoxyethane; and the chlorinated linear ether solvent is a compound with formula (I): (I); wherein R1 is selected from C1-C4 chlorinated alkyl, and R2 is selected from C1-C4 alkyl and C1-C4 chlorinated alkyl. The application solves the problem that the interface stability of the electrolyte in the prior art lithium metal battery is insufficient, and the capacity retention rate in a long-period cycle process is poor and the coulombic efficiency of a lithium-copper half battery is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium metal battery technology, and more specifically, to an electrolyte and a lithium metal battery. Background Technology

[0002] Currently, in traditional electrolyte systems, lithium metal undergoes violent side reactions with solvents and lithium salts during repeated charge and discharge processes, generating a loosely structured solid electrolyte interphase (SEI) film with low mechanical strength. This SEI film is difficult to effectively suppress the growth of lithium dendrites, resulting in a decline in the cycle performance of lithium metal batteries and posing serious safety hazards.

[0003] To improve SEI film performance, a high-concentration electrolyte strategy has been proposed. This strategy significantly increases the lithium salt concentration, forcing anions into the primary solvation sheath of lithium ions. During the reduction process at the negative electrode, these anions preferentially decompose to form a dense SEI film rich in inorganic components (such as LiF and Li₂O), thereby improving the uniformity and reversibility of lithium deposition. However, high-concentration electrolytes suffer from high viscosity, low conductivity, high cost, and poor wettability, severely limiting their large-scale application. Therefore, a localized high-concentration electrolyte approach introduces chemically inert, low-solvation-capacity diluents (such as fluorinated ethers). This approach retains the high-concentration solvation structure while reducing system viscosity and increasing ion mobility, significantly improving the overall performance of the electrolyte. Nevertheless, current local high-concentration electrolyte systems still mainly rely on fluorinated solvents to generate SEI films dominated by LiF. Although LiF has a high modulus, its interfacial energy is low and its ionic conductivity is limited, making it difficult to achieve long-term dynamic stability of lithium deposition. Furthermore, the existing SEI film composition still lacks precise control over specific inorganic components (such as LiCl), which makes the SEI film prone to failure during cycling due to component dissolution and structural collapse, making it impossible to maintain capacity retention and high coulombic efficiency of lithium copper half-cells under long-term cycling.

[0004] Although existing electrolyte systems have optimized their physicochemical properties through local high-concentration design, they still fail to effectively solve the problem of continuous dissolution and loss of key inorganic components (such as lithium chloride) in the SEI film. This leads to the gradual deterioration of the interface structure with cycling, making it difficult to maintain the reversibility of lithium deposition / stripping. Consequently, lithium metal batteries suffer from poor capacity retention under long-cycle cycling, and the coulombic efficiency of lithium copper half-cells decays. Summary of the Invention

[0005] The main objective of this invention is to provide an electrolyte that solves the problem of insufficient interfacial stability of electrolytes in existing lithium metal batteries, which leads to poor capacity retention and decay of coulombic efficiency in lithium copper half-cells during long-cycle cycles.

[0006] To achieve the above objectives, according to one aspect of the present invention, an electrolyte is provided, comprising a lithium salt and an ether solvent; wherein the lithium salt comprises sulfonylimide lithium salt and fluoroborate lithium salt, and the molar ratio of sulfonylimide lithium salt to fluoroborate lithium salt is 1:(0.1~0.5); the ether solvent comprises linear ether solvent and chlorolinear ether solvent; the linear ether solvent comprises at least one selected from 1,2-dimethoxypropane, 1,3-dimethoxypropane, 1,2-diethoxyethane, and 1-methoxy-2-ethoxyethane; the chlorolinear ether solvent is a compound having formula (I):

[0007] (I);

[0008] Wherein, R1 is selected from C1~C4 chloroalkyl, and R2 is selected from any one of C1~C4 alkyl and C1~C4 chloroalkyl.

[0009] Furthermore, R1 is selected from any one of chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl; R2 is selected from any one of methyl, ethyl, chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl.

[0010] Furthermore, R1 is selected from chloromethyl; R2 is selected from methyl or chloromethyl.

[0011] Further, the chlorinated linear ether solvent is selected from 1-methoxy-2-(chloromethoxy)propane, 1-ethoxy-2-(chloromethoxy)propane, 1-(chloromethoxy)-2-(chloromethoxy)propane, 1-(2-chloroethoxy)-2-(chloromethoxy)propane, 1-(1,1-dichloroethoxy)-2-(chloromethoxy)propane, 1-methoxy-2-(2-chloroethoxy)propane, 1-ethoxy-2-(2-chloroethoxy)propane, 1-(chloromethoxy)-2-(2-chloroethoxy)propane, 1-(2 At least one of the following: 1-(1,1-dichloroethoxy)-2-(2-chloroethoxy)propane, 1-methoxy-2-(1,1-dichloroethoxy)propane, 1-ethoxy-2-(1,1-dichloroethoxy)propane, 1-(chloromethoxy)-2-(1,1-dichloroethoxy)propane, 1-(2-chloroethoxy)-2-(1,1-dichloroethoxy)propane, and 1-(1,1-dichloroethoxy)-2-(1,1-dichloroethoxy)propane.

[0012] Furthermore, the electrolyte also includes a diluent, including fluorinated ether diluents.

[0013] More preferably, the fluorinated ether diluent includes at least one of tris(trifluoroethoxy)methane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-1,2,2,2-tetrafluoroethyl ether, and trifluoromethylethyl ether.

[0014] Furthermore, the molar ratio of sulfonylimide lithium salt to diluent is 1:(2~5).

[0015] Furthermore, sulfonylimide lithium salts include at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(ethylsulfonyl)imide; fluoroborate lithium salts include at least one of lithium difluorooxalateborate and lithium tetrafluoroborate.

[0016] Furthermore, the molar ratio of sulfonylimide lithium salt to linear ether solvent is 1:(1.5~3).

[0017] Furthermore, the molar ratio of sulfonylimide lithium salt to chlorinated linear ether is 1:(0.1~1).

[0018] In a second aspect, the present invention provides a lithium metal battery, comprising a positive electrode, a separator, an electrolyte, and a lithium metal negative electrode, wherein the separator is located between the positive electrode and the lithium metal negative electrode, and the electrolyte comprises any of the electrolytes described above.

[0019] By employing the technical solution of this invention, a composite lithium salt system composed of sulfonylimide lithium salt and fluoroborate lithium salt in a specific molar ratio of 1:(0.1~0.5), combined with an ether solvent system composed of a linear ether solvent and a chlorinated linear ether solvent with the structure of formula (I), can be formed at both the negative electrode and the positive electrode, while improving the ion conductivity of the electrolyte. This effectively inhibits aluminum foil corrosion and reduces interfacial impedance. Furthermore, by introducing a chlorinated linear ether solvent with a specific structure into the weak solvation environment provided by the linear ether solvent, the solvation sheath structure of lithium ions can be further controlled, promoting the reduction and decomposition of the chlorinated linear ether solvent on the negative electrode surface, generating an in-situ lithium chloride-rich SEI film, thereby helping to suppress lithium dendrite growth and interfacial side reactions. The dual lithium salt system of the electrolyte in this invention works synergistically with ether solvents to enable the electrolyte to simultaneously maintain ion conductivity and electrode interface stability, thereby reducing active lithium loss and capacity decay during cycling, and ultimately improving the capacity retention rate of lithium metal batteries under high-voltage long-cycle conditions and the coulombic efficiency of lithium copper half-cells. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0021] As described in the background section of this invention, existing technologies suffer from insufficient interfacial stability of the electrolyte in lithium metal batteries, leading to poor capacity retention and coulombic efficiency decay in lithium copper half-cells during long-cycle periods. To address these issues, in a typical embodiment of this invention, an electrolyte is provided, comprising a lithium salt and an ether solvent; wherein the lithium salt comprises sulfonylimide lithium salts and fluoroborate lithium salts, and the molar ratio of sulfonylimide lithium salt to fluoroborate lithium salt is 1:(0.1~0.5); the ether solvent comprises linear ether solvents and chlorolinear ether solvents; the linear ether solvent comprises at least one of 1,2-dimethoxypropane, 1,3-dimethoxypropane, 1,2-diethoxyethane, and 1-methoxy-2-ethoxyethane; the chlorolinear ether solvent is a compound having formula (I):

[0022] (I);

[0023] Wherein, R1 is selected from C1~C4 chloroalkyl, and R2 is selected from any one of C1~C4 alkyl and C1~C4 chloroalkyl.

[0024] The electrolyte of this invention is mainly used in lithium metal batteries, which include electrode components and an electrolyte. The electrode components include a positive electrode, a lithium metal negative electrode, and a separator. The separator is disposed between the positive electrode and the lithium metal negative electrode, and the lithium metal negative electrode includes a copper current collector and a lithium metal layer supported on the copper current collector. The electrolyte plays a role in conducting lithium ions between the positive electrode and the lithium metal negative electrode and can participate in the formation of the CEI and SEI films. Because the lithium metal negative electrode is prone to interfacial side reactions, lithium dendrite growth, and loss of active lithium during cycling, it is necessary to adjust the electrolyte system to improve the stability of the positive and negative electrode interface, thereby improving the capacity retention rate of the lithium metal battery and the coulombic efficiency of the lithium copper half-cell.

[0025] The electrolyte of this invention comprises lithium salts and ether solvents, with the lithium salts including sulfonylimide lithium salts and fluoroborate lithium salts. Sulfonylimide lithium salts exhibit good dissociation ability and low viscosity, providing a large number of migratable lithium ions in the electrolyte, thus improving the ion conductivity of the electrolyte. Simultaneously, sulfonylimide lithium salts also possess excellent SEI film-forming ability, promoting uniform lithium ion deposition. Fluoroborate lithium salts, on the other hand, facilitate the formation of a stable CEI film on the positive electrode surface, thereby helping to reduce and stabilize interfacial impedance. Furthermore, the addition of fluoroborate lithium salts can, to some extent, alleviate the problem of monotonous interfacial film composition and volatile interfaces in single-lithium salt systems. In addition, fluoroborate lithium salts can effectively inhibit the corrosion of the positive electrode aluminum current collector by sulfonylimide lithium salts, thereby improving the long-term stability of lithium metal batteries under high-voltage conditions. The present invention further limits the molar ratio of sulfonylimide lithium salt to fluoroborate lithium salt to 1: (0.1~0.5). This range can ensure that fluoroborate lithium salt can effectively play its role in improving the interface, while reducing the adverse effects of excessive fluoroborate lithium salt on the ion transport and overall stability of the electrolyte system, thereby taking into account both ion conduction capacity and interface stability.

[0026] The ether solvents of this invention include linear ether solvents and chlorolinear ether solvents. The linear ether solvents exhibit good fluidity and low viscosity, which facilitates the dissolution of lithium salts and provides a favorable liquid-phase migration environment for lithium ions. Linear ether solvents also improve the wettability and mass transfer capacity of the electrolyte, thereby mitigating the conduction limitation problem caused by excessively high solvent viscosity in the electrolyte. Simultaneously, linear ether solvents can participate in the initial solvation of lithium ions, influencing the migration state of lithium ions, interfacial solvation behavior, and subsequent interfacial film formation. Because the interaction between linear ether solvents and lithium ions is relatively weak, it is beneficial to encourage more lithium salt anions to enter the primary solvation sheath layer of lithium ions, thus providing a basis for the formation of anion-derived SEI films.

[0027] Compared to linear ether solvents, chlorinated linear ether solvents, in addition to participating in lithium salt dissolution and lithium-ion solvation, also have an interface regulation effect. Because chlorinated linear ether solvent molecules contain chlorinated structures, they are more likely to participate in the formation of the SEI film and are beneficial for building a more stable SEI film on the lithium metal anode surface. During the first charging process of the lithium metal anode, the chlorinated linear ether solvent can undergo reduction decomposition on the lithium metal anode surface, thereby generating an in-situ lithium chloride (LiCl)-rich SEI film. LiCl, as an inorganic interface component, has high ionic conductivity and interfacial energy, which can effectively guide the uniform deposition of lithium metal and inhibit dendrite growth. Therefore, chlorinated linear ether solvents can not only improve the chemical stability of the anode interface but also improve its mechanical stability and long-term cycling stability, thus contributing to improving the capacity retention rate of lithium metal batteries under long-cycle conditions. Furthermore, this invention defines the chlorinated linear ether solvent using formula (I) and limits the substituent ranges of R1 and R2. This limiting method allows chlorolinear ether solvents to retain both the interfacial control capabilities afforded by the chlorostructure and the tunable space of the molecular structure. Different substituents can affect the polarity, steric hindrance, and interfacial participation ability of the molecule; therefore, this general formula limitation is beneficial for maintaining good applicability and stability of chlorolinear ether solvents in electrolytes.

[0028] Therefore, by limiting the lithium salt in the electrolyte to a combination of sulfonylimide lithium salt and fluoroborate lithium salt, and controlling their molar ratio, it is possible to improve the ion conductivity of the electrolyte while forming stable SEI and CEI films, effectively suppressing aluminum foil corrosion and reducing interfacial impedance. Furthermore, by introducing a chlorinated linear ether solvent with a specific structure into the weak solvation environment provided by the linear ether solvent, it is helpful to further regulate the solvation sheath structure of lithium ions, promoting the reduction and decomposition of the chlorinated linear ether solvent on the negative electrode surface, and generating an in-situ lithium chloride-rich SEI film, thereby helping to suppress lithium dendrite growth and interfacial side reactions. The dual lithium salt system and ether solvent of the electrolyte of this invention work synergistically to enable the electrolyte to simultaneously maintain ion conductivity and electrode interfacial stability, thereby reducing active lithium loss and capacity decay during cycling, ultimately improving the capacity retention rate of lithium metal batteries under high-voltage long-cycle conditions and the coulombic efficiency of lithium copper half-cells.

[0029] In some embodiments, R1 is selected from any one of chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl; R2 is selected from any one of methyl, ethyl, chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl. By controlling the substituent types of R1 and R2 in the chlorolinear ether solvent, it is helpful to improve the reduction activity and selectivity of the chlorolinear ether solvent on the lithium metal anode surface, which helps to further generate high-purity and high-density lithium chloride components in situ, and makes the generated LiCl more uniformly distributed and more crystallinity in the SEI film, thereby helping to enhance the chemical stability of the electrolyte.

[0030] In some preferred embodiments, R1 is selected from chloromethyl; R2 is selected from methyl or chloromethyl. By further controlling that R1 in the chlorolinear ether solvent is selected from chloromethyl and R2 is selected from methyl or chloromethyl, it is helpful to further improve the efficiency of chlorine release during the electrochemical reduction process of the chlorolinear ether solvent, to further form a more uniformly distributed lithium chloride-rich SEI film on the lithium metal anode surface, and to further enhance the interfacial film's ability to suppress lithium dendrites, thereby helping to improve the cycle stability of the lithium metal battery.

[0031] In some embodiments, the chlorolinear ether solvent is selected from 1-methoxy-2-(chloromethoxy)propane, 1-ethoxy-2-(chloromethoxy)propane, 1-(chloromethoxy)-2-(chloromethoxy)propane, 1-(2-chloroethoxy)-2-(chloromethoxy)propane, 1-(1,1-dichloroethoxy)-2-(chloromethoxy)propane, 1-methoxy-2-(2-chloroethoxy)propane, 1-ethoxy-2-(2-chloroethoxy)propane, 1-(chloromethoxy)-2-(2-chloroethoxy)propane, 1- At least one of (2-chloroethoxy)-2-(2-chloroethoxy)propane, 1-(1,1-dichloroethoxy)-2-(2-chloroethoxy)propane, 1-methoxy-2-(1,1-dichloroethoxy)propane, 1-ethoxy-2-(1,1-dichloroethoxy)propane, 1-(chloromethoxy)-2-(1,1-dichloroethoxy)propane, 1-(2-chloroethoxy)-2-(1,1-dichloroethoxy)propane, and 1-(1,1-dichloroethoxy)-2-(1,1-dichloroethoxy)propane. By controlling the specific compounds of the chlorolinear ether solvent, the selected structures exhibit precisely tunable chlorine atom distribution and spatial configuration. This facilitates the efficient reduction of lithium chloride components with high chemical stability and low solubility on the lithium metal anode surface. Furthermore, it helps to synergistically construct a dense, uniform, weakly solvated sheath layer with sulfonylimide and fluoroboronic acid lithium salts, further suppressing the erosion and dissolution of the SEI film by electrolyte components. In addition, the chloroalkyl radical intermediates formed during the reduction process by the chloroether solvent have stable structures, helping to reduce interfacial inhomogeneities or localized lithium chloride loss caused by uncertain chlorine substitution sites. This contributes to improving the enrichment and structural continuity of lithium chloride in the SEI film, further enhancing the chemical and cycling stability of the anode interface.

[0032] In some embodiments, the electrolyte further includes a diluent, including fluorinated ether diluents. By further introducing diluent components into the electrolyte and controlling their types, it is helpful to further adjust the viscosity and flowability of the electrolyte system, further improve the wettability and mass transfer capacity of the electrolyte, thereby helping to optimize the stability of the electrolyte under high pressure conditions and improve the capacity retention of lithium metal batteries and the coulombic efficiency of lithium copper half-cells.

[0033] In some preferred embodiments, the fluorinated ether diluent includes at least one of tris(trifluoroethoxy)methane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-1,2,2,2-tetrafluoroethyl ether, and trifluoromethylethyl ether. Further controlling the specific type of fluorinated ether diluent helps to further improve the oxidative stability and system compatibility of the diluent, and helps to regulate the solvation environment and interface state. Simultaneously, this type of fluorinated ether diluent does not participate in the primary solvation sheath structure of lithium ions, which helps to improve the stability of the lithium chloride component in the SEI film, thereby helping to reduce electrolyte decomposition and continuous corrosion of the lithium metal anode under high-voltage cathode conditions. Furthermore, the low polarity and high fluorine content of the fluorinated ether diluent helps to enhance the compatibility of the electrolyte with high-voltage cathode materials, and helps to further improve the interface stability of the lithium metal battery during long-cycle processes, thereby helping to improve the capacity retention rate of the lithium metal battery.

[0034] In some embodiments, the molar ratio of sulfonylimide lithium salt to diluent is 1:(2~5). By controlling the amount of diluent added, it is helpful to adjust the viscosity, flowability, and solvation environment of the electrolyte, and to reduce the problem of excessive diluent damaging the stability of the primary solvation sheath of lithium ions. This helps to improve the thermodynamic stability of the lithium chloride-rich SEI film, and further reduces the dissolution and loss of lithium chloride components due to disturbances in the local solvation environment. At the same time, this ratio range helps the diluent to further reduce electrolyte viscosity and improve ion transport, ultimately helping to improve the long-term stability and cycle life of the lithium metal anode interface film. Specifically, the molar ratio of sulfonylimide lithium salt to diluent can be 1:2, 1:3, 1:3.5, 1:4, 1:5, or any combination thereof.

[0035] In some embodiments, sulfonylimide lithium salts include at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(ethylsulfonyl)imide; fluoroborate lithium salts include at least one of lithium difluorooxalate borate and lithium tetrafluoroborate. By controlling the specific types of sulfonylimide and fluoroborate lithium salts in the electrolyte, it is helpful to further optimize the electrolyte's dissociation capacity, ion conductivity, and interfacial film-forming properties, thereby helping to improve the capacity retention of lithium metal batteries under high-voltage, long-cycle conditions. Simultaneously, it helps to further improve the viscosity level and ion conductivity of the lithium salt system, and further improves the polarization and capacity decay behavior during lithium metal battery cycling.

[0036] In some embodiments of the present invention, without departing from the inventive concept, the electrolyte may include, in addition to the aforementioned sulfonylimide lithium salts and fluoroborate lithium salts, other functional lithium salts or additives (such as lithium difluorophosphate, lithium bis(oxalato)borate, etc.) as needed. These other functional lithium salts or additives can be used to further adjust the physicochemical properties, interface state, or safety performance of the electrolyte, but do not change the core technical solution of the present invention, which involves forming a composite lithium salt system with sulfonylimide lithium salts and fluoroborate lithium salts in a specific molar ratio, and coordinating its action with ether solvents.

[0037] In some embodiments, the molar ratio of sulfonylimide lithium salt to linear ether solvent is 1:(1.5~3). By controlling the molar ratio of sulfonylimide lithium salt to linear ether solvent, it is helpful to control the relative content of linear ether solvent in the electrolyte. Combined with a specific molar ratio of sulfonylimide lithium salt to fluoroborate lithium salt, this helps lithium salt anions to dominate in the primary solvation sheath layer of lithium ions, and also helps to regulate the participation of chlorinated linear ether in the sheath layer, thereby facilitating the further formation of an SEI film with lithium chloride as the key component. At the same time, this ratio range helps to improve the sufficient deposition of lithium chloride during the SEI film formation process, helps to reduce the solvation and dissolution effect of excess linear ether solvent on lithium chloride, further improves the chemical stability and structural integrity of the SEI film, helps to reduce the dissolution and loss of lithium chloride component in the SEI film during cycling, and thus helps to enhance the interfacial compatibility and electrochemical stability of the electrolyte in the highly active lithium metal system. Specifically, the molar ratio of sulfonylimide lithium salt to linear ether solvent can be 1:1.5, 1:1.8, 1:2, 1:2.5, 1:2.8, 1:3, or any combination thereof.

[0038] In some embodiments, the molar ratio of sulfonylimide lithium salt to chlorinated linear ether is 1:(0.1~1). By controlling the molar ratio of sulfonylimide lithium salt to chlorinated linear ether solvent, it is helpful to control the proportion of chlorinated linear ether solvent in the primary solvation sheath of lithium ions, thereby helping to regulate the reduction behavior of chlorinated linear ether solvent on the lithium metal anode surface and promoting the participation of lithium chloride component in the construction of SEI film in a uniform and dense manner. At the same time, this ratio range helps to reduce the problem of insufficient lithium chloride formation due to excessively low chlorinated linear ether content, resulting in poor chemical stability and easy dissolution and loss of SEI film. It also helps to reduce the problem of excessively high chlorinated linear ether content causing electrolyte oxidation decomposition or aggravated side reactions, thereby damaging the mechanical integrity and ion conduction uniformity of SEI film. The synergistic effect of chlorinated linear ethers with sulfonylimide lithium salts and fluoroborate lithium salts helps to further optimize the composition ratio and distribution of inorganic components in the SEI film, improves the chemical stability and interfacial durability of the SEI film during cycling, and thus contributes to the stable deposition and dissolution behavior of lithium metal anodes under high current density and long-term service, helps to reduce the risk of dendrite growth and electrolyte consumption, and further helps to improve the capacity retention rate of lithium metal batteries and the coulombic efficiency of lithium copper half-cells. Specifically, the molar ratio of sulfonylimide lithium salt to chlorinated linear ether can be 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1, or any combination thereof.

[0039] In a second aspect, the present invention provides a lithium metal battery, comprising a positive electrode, a separator, an electrolyte, and a lithium metal negative electrode, wherein the separator is located between the positive electrode and the lithium metal negative electrode, and the electrolyte comprises any of the electrolytes described above.

[0040] The use of the aforementioned high-performance electrolyte enables lithium metal batteries to possess both good ion conductivity and a stable interface film. Specifically, the positive electrode surface helps to form a stable CEI film, while the lithium metal negative electrode surface helps to form a stable SEI film rich in lithium chloride. This helps to suppress interfacial side reactions and lithium dendrite growth, reduce capacity decay during cycling, and further improve the capacity retention rate of lithium metal batteries under high-voltage long-cycle conditions and the coulombic efficiency of lithium copper half-cells.

[0041] The present invention will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention.

[0042] Example 1

[0043] This embodiment provides an electrolyte comprising a lithium salt, a linear ether solvent, a chlorinated linear ether solvent, and a diluent. The specific components are as follows:

[0044] (1) The lithium salt is lithium difluorosulfonylimide and lithium difluorooxalate borate, and the molar ratio of lithium difluorosulfonylimide and lithium difluorooxalate borate is 1:0.2;

[0045] (2) The linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.6;

[0046] (3) In the chlorinated linear ether solvent, R1 is a chloromethyl substituent and R2 is a methyl substituent, that is, the chlorinated linear ether solvent is 1-methoxy-2-(chloromethoxy)propane, and the molar ratio of lithium difluorosulfonylimide to 1-methoxy-2-(chloromethoxy)propane is 1:0.4.

[0047] (4) The diluent is tri(trifluoroethoxy)methane, and the molar ratio of lithium difluorosulfonylimide to tri(trifluoroethoxy)methane is 1:4.

[0048] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0049] Example 2

[0050] The difference from Example 1 is that the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.5; and the molar ratio of lithium bis(fluorosulfonyl)imide to 1-methoxy-2-(chloromethoxy)propane is 1:0.5.

[0051] Example 3

[0052] The difference from Example 1 is as follows:

[0053] (1) The molar ratio of lithium difluorosulfonylimide to lithium difluorooxalate borate is 1:0.3;

[0054] (2) The molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.8;

[0055] (3) The molar ratio of lithium bis(fluorosulfonyl)imide to 1-methoxy-2-(chloromethoxy)propane is 1:0.6;

[0056] (4) The molar ratio of lithium bis(fluorosulfonyl)imide to tris(trifluoroethoxy)methane is 1:3.

[0057] Example 4

[0058] The difference from Example 1 is as follows:

[0059] (1) The molar ratio of lithium difluorosulfonylimide to lithium difluorooxalate borate is 1:0.5;

[0060] (2) The molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:3;

[0061] (3) The molar ratio of lithium bis(fluorosulfonyl)imide to 1-methoxy-2-(chloromethoxy)propane is 1:1;

[0062] (4) The molar ratio of lithium difluorosulfonylimide to tris(trifluoroethoxy)methane is 1:5.

[0063] Example 5

[0064] The difference from Example 1 is as follows:

[0065] (1) The molar ratio of lithium difluorosulfonylimide to lithium difluorooxalate borate is 1:0.1;

[0066] (2) The molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.5;

[0067] (3) The molar ratio of lithium bis(fluorosulfonyl)imide to 1-methoxy-2-(chloromethoxy)propane is 1:0.1;

[0068] (4) The molar ratio of lithium bis(fluorosulfonyl)imide to tris(trifluoroethoxy)methane is 1:2.

[0069] Example 6

[0070] The difference from Example 1 is that R1 is a chloromethyl substituent and R2 is a chloromethyl substituent in the chlorolinear ether solvent, that is, the chlorolinear ether solvent is 1-(chloromethoxy)-2-(chloromethoxy)propane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1-(chloromethoxy)-2-(chloromethoxy)propane is 1:0.4.

[0071] Example 7

[0072] The difference from Example 1 is that the R1 substituent in the chlorinated linear ether solvent is 2-chloroethyl and the R2 substituent is chloromethyl, that is, the chlorinated linear ether solvent is 1-(chloromethoxy)-2-(2-chloroethoxy)propane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1-(chloromethoxy)-2-(2-chloroethoxy)propane is 1:0.4.

[0073] Example 8

[0074] The difference from Example 1 is that R1 is a 2-chloroethyl substituent in the chlorolinear ether solvent and R2 is an ethyl substituent, that is, the chlorolinear ether solvent is 1-ethoxy-2-(2-chloroethoxy)propane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1-ethoxy-2-(2-chloroethoxy)propane is 1:0.4.

[0075] Example 9

[0076] The difference from Example 1 is that this example provides an electrolyte that includes lithium salt, linear ether solvent, and chlorinated linear ether solvent, but does not include diluent. The types and proportions of the remaining components are the same as in Example 1.

[0077] Example 10

[0078] The difference from Example 1 is that the linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:5.

[0079] Example 11

[0080] The difference from Example 1 is that the molar ratio of lithium bis(fluorosulfonyl)imide to 1-methoxy-2-(chloromethoxy)propane is 1:3.

[0081] Example 12

[0082] The difference from Example 1 is that the molar ratio of lithium bis(fluorosulfonyl)imide to tris(trifluoroethoxy)methane is 1:8.

[0083] Comparative Example 1

[0084] This comparative example provides an electrolyte comprising a lithium salt, a linear ether solvent, and a diluent. The specific components are as follows:

[0085] (1) The lithium salt is lithium difluorosulfonylimide and lithium difluorooxalate borate, and the molar ratio of lithium difluorosulfonylimide and lithium difluorooxalate borate is 1:0.2;

[0086] (2) The linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.6;

[0087] (3) The diluent is tris(trifluoroethoxy)methane, and the molar ratio of lithium difluorosulfonylimide to tris(trifluoroethoxy)methane is 1:4.

[0088] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0089] Comparative Example 2

[0090] This comparative example provides an electrolyte comprising a lithium salt, a chlorinated linear ether solvent, and a diluent. The specific components are as follows:

[0091] (1) The lithium salt is lithium difluorosulfonylimide and lithium difluorooxalate borate, and the molar ratio of lithium difluorosulfonylimide and lithium difluorooxalate borate is 1:0.2;

[0092] (2) In the chlorinated linear ether solvent, R1 is chloromethyl and R2 is methyl, that is, the chlorinated linear ether solvent is 1-methoxy-2-(chloromethoxy)propane, and the molar ratio of lithium difluorosulfonylimide to 1-methoxy-2-(chloromethoxy)propane is 1:0.4.

[0093] (3) The diluent is tris(trifluoroethoxy)methane, and the molar ratio of lithium difluorosulfonylimide to tris(trifluoroethoxy)methane is 1:4.

[0094] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0095] Comparative Example 3

[0096] This comparative example provides an electrolyte comprising a lithium salt, a linear ether solvent, a chlorinated linear ether solvent, and a diluent. The specific components are as follows:

[0097] (1) The lithium salt is lithium difluorosulfonylimide;

[0098] (2) The linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.6;

[0099] (3) In the chlorinated linear ether solvent, R1 is a chloromethyl substituent and R2 is a methyl substituent, that is, the chlorinated linear ether solvent is 1-methoxy-2-(chloromethoxy)propane, and the molar ratio of lithium difluorosulfonylimide to 1-methoxy-2-(chloromethoxy)propane is 1:0.4.

[0100] (4) The diluent is tri(trifluoroethoxy)methane, and the molar ratio of lithium difluorosulfonylimide to tri(trifluoroethoxy)methane is 1:4.

[0101] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0102] Comparative Example 4

[0103] This comparative example provides an electrolyte comprising a lithium salt, a linear ether solvent, a chlorinated linear ether solvent, and a diluent. The specific components are as follows:

[0104] (1) The lithium salt is lithium difluorooxalate borate;

[0105] (2) The linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium salt to 1,2-dimethoxypropane is 1:1.6;

[0106] (3) In the chlorolinear ether solvent, R1 is a chloromethyl substituent and R2 is a methyl substituent, that is, the chlorolinear ether solvent is 1-methoxy-2-(chloromethoxy)propane, and the molar ratio of lithium salt to 1-methoxy-2-(chloromethoxy)propane is 1:0.4.

[0107] (4) The diluent is tris(trifluoroethoxy)methane, and the molar ratio of lithium salt to tris(trifluoroethoxy)methane is 1:4.

[0108] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0109] Comparative Example 5

[0110] This comparative example provides an electrolyte comprising a lithium salt, a linear ether solvent, a chlorinated linear ether solvent, and a diluent. The specific components are as follows:

[0111] (1) The lithium salt is lithium difluorosulfonylimide and lithium difluorooxalate borate, and the molar ratio of lithium difluorosulfonylimide and lithium difluorooxalate borate is 0.1:2;

[0112] (2) The linear ether solvent is 1,2-dimethoxypropane, and the molar ratio of lithium bis(fluorosulfonyl)imide to 1,2-dimethoxypropane is 1:1.6;

[0113] (3) In the chlorinated linear ether solvent, R1 is a chloromethyl substituent and R2 is a methyl substituent, that is, the chlorinated linear ether solvent is 1-methoxy-2-(chloromethoxy)propane, and the molar ratio of lithium difluorosulfonylimide to 1-methoxy-2-(chloromethoxy)propane is 1:0.4.

[0114] (4) The diluent is tri(trifluoroethoxy)methane, and the molar ratio of lithium difluorosulfonylimide to tri(trifluoroethoxy)methane is 1:4.

[0115] Under an argon atmosphere where the water and oxygen content both do not exceed 0.1 ppm, the above substances are mixed according to the stoichiometric ratio and stirred continuously at room temperature for 30 minutes to obtain an electrolyte.

[0116] Test methods

[0117] 1. Preparation of lithium metal batteries:

[0118] The lithium metal anode comprises a copper current collector and a lithium metal layer supported on the copper current collector. The lithium metal layer has a thickness of 30 μm, and the copper current collector has a thickness of 8 μm. The cathode comprises lithium nickel cobalt manganese oxide (LiNiO2) as the cathode active material. 0.8 Co 0.1 Mn 0.1O2), binder polyvinylidene fluoride, conductive agent conductive carbon black, and current collector aluminum foil. Among them, LiNi 0.8 Co 0.1 Mn 0.1 The mass ratio of O2, polyvinylidene fluoride, and conductive carbon black is 8:1:1; the thickness of the current collector aluminum foil is 11 μm; and the areal capacity of the positive electrode active material is 2.0 mAh / cm². 2 The separator is a polypropylene membrane with a thickness of 25 μm. Under an argon atmosphere with water and oxygen content not exceeding 0.1 ppm, the positive electrode, separator, and lithium metal negative electrode are assembled into a single-layer soft-pack battery cell using a stacking process, and then injected with the electrolytes of Examples 1-12 and Comparative Examples 1-5. The electrolyte injection coefficient is 20 g / Ah.

[0119] 2. Capacity retention test:

[0120] The lithium metal batteries of Examples 1-12 and Comparative Examples 1-5 were subjected to charge-discharge tests at 25°C. The charge-discharge voltage range of the lithium metal batteries was 3V~4.3V. The charge-discharge rate during formation was 0.1C, and the batteries were cycled for 2 cycles. During long-term cycling, the charge-discharge rate was 0.5C. The capacity retention rate of the lithium metal batteries after 200 cycles was calculated. The capacity retention rate (%) after the 200th cycle was calculated as: (200th discharge capacity / first discharge capacity) × 100%. The test results are shown in Table 1.

[0121] 3. Coulombic efficiency test of lithium copper half-cell:

[0122] The CR2032 coin cell system was used. The working electrode was a polished and clean copper foil (Cu); the counter electrode was lithium metal with a thickness of 100 μm; the separator and electrolyte were the same polypropylene separator and electrolyte used in the examples / comparative examples as in the full cell.

[0123] The coulombic efficiency of the lithium copper half-cells of Examples 1-12 and Comparative Examples 1-5 was tested at 25°C. The efficiency was measured at 0.5 mA / cm². 2 The current density of lithium deposited on copper foil is 2 mAh / cm². 2 The charge (Qd) was then stripped from the copper foil surface at the same current density until the voltage rose to the cutoff voltage of 1.0V, and the total charge Qs stripped was recorded.

[0124] Calculation formula: Coulomb efficiency (CE) = stripping charge Qs / deposition charge Qd × 100%.

[0125] The result is taken as the average value from the 10th to the 50th cycle (after the interface film has stabilized) as the stable coulombic efficiency of the electrolyte system. The test results are shown in Table 1.

[0126] Table 1

[0127]

[0128] As shown in Table 1, compared to Comparative Examples 1-5, Examples 1-12, due to the use of a composite lithium salt system composed of sulfonylimide lithium salt and fluoroborate lithium salt, combined with linear ether solvent and chlorinated linear ether solvent, enable the electrolyte to balance lithium-ion conductivity, positive electrode interface stability, and lithium metal negative electrode interface stability. This helps to form a stable lithium chloride-rich SEI film on the lithium metal negative electrode surface, reducing active lithium loss and capacity decay during cycling. Therefore, the lithium metal batteries prepared with the electrolytes obtained in Examples 1-12 exhibit a capacity retention of ≥82.5% after 200 cycles, demonstrating that the electrolyte of this invention has excellent long-cycle performance. Furthermore, in lithium metal battery research, the coulombic efficiency of the lithium-copper half-cell quantifies the retention rate of active lithium during cycling and is a key a priori indicator for accurately predicting the lifespan of the full cell under high-voltage long-cycle conditions. Meanwhile, the high coulombic efficiency directly reflects the high degree of reversibility of the interface (or the degree of reversibility of lithium deposition / stripping) of the LiCl-rich interfacial film generated in situ in this invention in maintaining high ion transport kinetics, inducing uniform lithium deposition, and effectively suppressing dendrite growth. It is a comprehensive indicator of the interfacial electrochemical stability of the electrolyte system. Therefore, the coulombic efficiency of the lithium-copper half-cells prepared with the electrolytes of Examples 1-12 of this invention is ≥93.2%, indicating that the electrolyte of this invention can balance lithium-ion conductivity, positive electrode interface stability, and lithium metal negative electrode interface stability.

[0129] Comparative Example 1, lacking a chlorinated linear ether solvent, struggled to effectively form a lithium chloride-rich SEI film in situ on the lithium metal anode surface. This resulted in reduced chemical and structural stability of the SEI film, increased side reactions during lithium deposition / stripping, and increased loss of active lithium. Consequently, after 200 cycles, the capacity retention was only 78.5%, and the coulombic efficiency of the lithium-copper half-cell was only 90.5%. Comparative Example 2, also lacking a linear ether solvent, struggled to provide a suitable weak solvation environment and favorable liquid-phase migration environment. This made it difficult to effectively control the solvation structure between lithium salt anions, the chlorinated linear ether solvent, and lithium ions, thus affecting the formation of a stable SEI film and the lithium-ion transport process. Consequently, after 200 cycles, the capacity retention was only 75.2%, and the coulombic efficiency of the lithium-copper half-cell was only 88.6%. Comparative Example 3, due to the absence of lithium difluorooxalate borate, lacked the effect of fluoroborate lithium salts in the electrolyte on the formation of the positive electrode interface film and the inhibition of corrosion of the aluminum current collector. This resulted in insufficient stability of the positive electrode interface during high-voltage cycling, which further aggravated the increase in interface impedance and capacity decay. Consequently, the capacity retention rate was only 82.4% after 200 cycles, and the coulombic efficiency of the lithium copper half-cell was only 92.8%.

[0130] Comparative Example 4, lacking lithium bis(fluorosulfonyl)imide, suffers from a deficiency in the electrolyte's dissociation and SEI film-forming capabilities due to the absence of sulfonylimide lithium salts. This results in decreased ion conductivity and difficulty in forming a stable anion-derived SEI film on the lithium metal anode surface, significantly reducing lithium deposition / stripping reversibility. Consequently, after 200 cycles, the capacity retention is only 65.4%, and the coulombic efficiency of the lithium-copper half-cell is only 82.1%. Comparative Example 5, while containing both lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate, has a molar ratio outside the limits specified in this application. This imbalance in the synergistic effect of sulfonylimide and fluoroborate lithium salts in the composite lithium salt system makes it difficult to simultaneously achieve a stable anode SEI film, a stable cathode CEI film, and high ion conductivity. Consequently, after 200 cycles, the capacity retention is only 69.1%, and the coulombic efficiency of the lithium-copper half-cell is only 85.3%.

[0131] Furthermore, compared to Example 9, Examples 1-8 further controlled the inclusion of a diluent in the electrolyte, specifically a fluorinated ether diluent. This helps reduce electrolyte viscosity, improve electrolyte wettability and mass transfer capacity, and helps maintain the stability of the locally high-concentration solvation structure, thereby making the SEI film formed on the lithium metal anode surface more stable and reducing active lithium loss. As a result, Examples 1-8 exhibited a capacity retention rate ≥91.2% and a coulombic efficiency ≥97.9% after 200 cycles. In contrast, Example 9, lacking a diluent, had relatively poor electrolyte fluidity, wettability, and ion transport performance, leading to decreased interfacial film stability and lithium deposition / stripping reversibility. Consequently, its capacity retention rate after 200 cycles was 82.5%, and its coulombic efficiency was 93.2%. Compared to Example 10, Examples 1-8 further controlled the molar ratio of sulfonylimide lithium salt to linear ether solvent within the range of 1:(1.5-3), which helps control the relative content of linear ether solvent in the electrolyte and, together with the composite lithium salt system and chlorinated linear ether solvent, forms a more stable solvation structure, thereby contributing to the formation of a stable and uniform SEI film. In Example 10, due to the molar ratio of lithium bis(fluorosulfonylimide) to 1,2-dimethoxypropane being 1:5, the linear ether solvent content was relatively high, which easily weakened the regulatory effect of lithium salt anions and chlorinated linear ether solvent on the lithium-ion solvation structure and interfacial film formation process, leading to a decrease in SEI film stability. Therefore, its capacity retention rate after 200 cycles was 88.5%, and the coulombic efficiency of the lithium copper half-cell was 96.8%.

[0132] Furthermore, compared to Example 11, Examples 1-8 further controlled the molar ratio of sulfonylimide lithium salt to chlorolinear ether solvent within the range of 1:(0.1~1), which helps to control the relative content of chlorolinear ether solvent in the electrolyte, allowing it to moderately participate in reduction film formation on the lithium metal anode surface and form a uniform and stable lithium chloride-rich SEI film. Therefore, Examples 1-8 achieved a capacity retention rate ≥91.2% and a coulombic efficiency ≥97.9% after 200 cycles. In contrast, Example 11, due to its 1:3 molar ratio of lithium bis(fluorosulfonylimide) to 1-methoxy-2-(chloromethoxy)propane and a high content of chlorolinear ether solvent, was prone to excessive reduction decomposition and interfacial side reactions, damaging the uniformity and structural integrity of the SEI film. Consequently, its capacity retention rate after 200 cycles was only 88.2%, and its coulombic efficiency was only 96.5%. Compared to Example 12, Examples 1-8 further controlled the molar ratio of sulfonylimide lithium salt to diluent within the range of 1:(2-5), which helps to maintain the stability of the primary solvation sheath layer of lithium ions while reducing electrolyte viscosity and improving wettability, thereby helping to improve the stability and continuity of the lithium chloride component in the SEI film. As a result, the capacity retention rate of Examples 1-8 after 200 cycles is ≥91.2%, and the coulombic efficiency of the lithium copper half-cell is ≥97.9%. However, in Example 12, due to the molar ratio of lithium bis(fluorosulfonylimide) to tris(trifluoroethoxy)methane being 1:8 and the high diluent content, it is easy to over-dilute the lithium ion solvation structure, reducing the participation of the effective film-forming components at the interface and resulting in a decrease in SEI film stability. Therefore, its capacity retention rate after 200 cycles is 86.8%, and the coulombic efficiency of the lithium copper half-cell is 95.4%.

[0133] Therefore, it can be seen that the present invention can significantly improve the long-cycle capacity retention and coulombic efficiency of lithium metal batteries through the synergistic combination of composite lithium salt system, linear ether solvent and chlorinated linear ether solvent; further, by adding fluorinated ether diluent and controlling the molar ratio of sulfonylimide lithium salt to linear ether solvent, chlorinated linear ether solvent and diluent, it is helpful to further improve the overall performance and interface stability of the electrolyte.

[0134] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An electrolyte, characterized in that, It includes lithium salts and ether solvents; wherein the lithium salts include sulfonylimide lithium salts and fluoroborate lithium salts, and the molar ratio of the sulfonylimide lithium salt to the fluoroborate lithium salt is 1:(0.1~0.5); The ether solvents include linear ether solvents and chlorinated linear ether solvents; The linear ether solvent includes at least one of 1,2-dimethoxypropane, 1,3-dimethoxypropane, 1,2-diethoxyethane, and 1-methoxy-2-ethoxyethane; The chlorinated linear ether solvent is a compound having formula (I): (Ⅰ); Wherein, R1 is selected from C1~C4 chloroalkyl, and R2 is selected from any one of C1~C4 alkyl and C1~C4 chloroalkyl.

2. The electrolyte according to claim 1, characterized in that, R1 is selected from any one of chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl; R2 is selected from any one of methyl, ethyl, chloromethyl, 2-chloroethyl, and 1,1-dichloroethyl.

3. The electrolyte according to claim 2, characterized in that, R1 is selected from chloromethyl; R2 is selected from methyl or chloromethyl.

4. The electrolyte according to claim 1, characterized in that, The chlorinated linear ether solvent is selected from 1-methoxy-2-(chloromethoxy)propane, 1-ethoxy-2-(chloromethoxy)propane, 1-(chloromethoxy)-2-(chloromethoxy)propane, 1-(2-chloroethoxy)-2-(chloromethoxy)propane, 1-(1,1-dichloroethoxy)-2-(chloromethoxy)propane, 1-methoxy-2-(2-chloroethoxy)propane, 1-ethoxy-2-(2-chloroethoxy)propane, 1-(chloromethoxy)-2-(2-chloroethoxy)propane, 1-(2- At least one of the following: chloroethoxy)-2-(2-chloroethoxy)propane, 1-(1,1-dichloroethoxy)-2-(2-chloroethoxy)propane, 1-methoxy-2-(1,1-dichloroethoxy)propane, 1-ethoxy-2-(1,1-dichloroethoxy)propane, 1-(chloromethoxy)-2-(1,1-dichloroethoxy)propane, 1-(2-chloroethoxy)-2-(1,1-dichloroethoxy)propane, and 1-(1,1-dichloroethoxy)-2-(1,1-dichloroethoxy)propane.

5. The electrolyte according to any one of claims 1 to 4, characterized in that, The electrolyte also includes a diluent, which includes fluorinated ether diluents; Preferably, the fluorinated ether diluent includes at least one of tris(trifluoroethoxy)methane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl-1,2,2,2-tetrafluoroethyl ether, and trifluoromethylethyl ether.

6. The electrolyte according to claim 5, characterized in that, The molar ratio of the sulfonylimide lithium salt to the diluent is 1:(2~5).

7. The electrolyte according to claim 5, characterized in that, The sulfonylimide lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(ethylsulfonyl)imide; the fluoroborate lithium salt includes at least one of lithium difluorooxalateborate and lithium tetrafluoroborate.

8. The electrolyte according to claim 6 or 7, characterized in that, The molar ratio of the sulfonamide lithium salt to the linear ether solvent is 1:(1.5~3).

9. The electrolyte according to claim 6 or 7, characterized in that, The molar ratio of the sulfonylimide lithium salt to the chlorinated linear ether solvent is 1:(0.1~1).

10. A lithium metal battery, characterized in that, The device includes a positive electrode, a separator, an electrolyte, and a lithium metal negative electrode, wherein the separator is located between the positive electrode and the lithium metal negative electrode, and the electrolyte includes the electrolyte according to any one of claims 1 to 9.